From: Kautsky, album I, no.11. With dedication from Bernstein to the Earl of Shouterfield, 1881, November 18 - Gut, Jean
From: Kautsky, album I, no.11. With dedication from Bernstein to the Earl of Shouterfield, 1881, November 18.